2022
DOI: 10.32890/mmj2022.26.6
|View full text |Cite
|
Sign up to set email alerts
|

Fraud Risk Management and Fraud Reduction

Abstract: The study examined the effect of fraud risk management techniques on fraud reduction in the oil and gas sector in Nigeria. The study used primary data which were obtained through a structured questionnaire. The population of the study consisted of 106 staff of the two top firms in the oil and gas sector in Nigeria. A total of 54 staff were purposively selected from the accounting department and 52 from the risk management department. They were selected due to their knowledge and expertise in field of study. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
0
0
1
Order By: Relevance
“…The results showed that all variables were weakly correlated with each other, with a maximum VIF of 1.954. It is similar to the tolerance level (Tol), and none of the variables reported a tolerance value of less than 0.05 (Mbasiti et al, 2021;Adebayo et al, 2022). Table . 2 shows the results test VIF and the Tolerance.…”
Section: Resultssupporting
confidence: 59%
“…The results showed that all variables were weakly correlated with each other, with a maximum VIF of 1.954. It is similar to the tolerance level (Tol), and none of the variables reported a tolerance value of less than 0.05 (Mbasiti et al, 2021;Adebayo et al, 2022). Table . 2 shows the results test VIF and the Tolerance.…”
Section: Resultssupporting
confidence: 59%
“…(Rationalization), faktor ini merupakan pembenaran tindakan fraud jika tidak adanya aturan yang jelas atau pengawasan yang jelas dari pihak perusahaan, merasa tidak ada yang dirugikan dengan dilakukan tindakan fraud, merasa ada tindakan fraud yang lebih besar atau parah daripada yang dilakukan saat ini, dan sebagainya. Dari skema fraud tersebut dapat ditemukan 3 kegiatan fraud yang umumnya terjadi pada perusahaan yaitu: korupsi, penyalahgunaan aset perusahaan dan manipulasi laporan keuangan (Adebayo et al, 2022).…”
Section: Pembenaranunclassified